Hydraulics of Overland Flow in Irrigation Borders under Rotational Running with a Watercourse - Sharma, R.K. (Journal of Soil and Water Conservation, 2022)
A study was carried out to analyse the hydraulics of overland flow into a border being irrigated in rotational running by a watercourse. The methodology was based on the consideration of important variables affecting the hydraulics of flow both at the border and the watercourse levels. The time-variable function of water infiltration rate was represented by its average value during the water-front advance. It was found that the ratio of average irrigation depth to the hydraulic depth of overland flow plays a key role in affecting the hydraulics of overland flow in borders being irrigated in rotational running with the watercourse.